2016
DOI: 10.5455/ja.20160726115117
|View full text |Cite
|
Sign up to set email alerts
|

Propolis as an alternative in prevention and control of dental cavity

Abstract: Propolis is a natural product, collected by bees from tree buds, flowers and pollen. It possesses various pharmaceutical properties, including antibacterial action against microorganisms involved in the beginning and progression of dental caries. This research aimed to analyze literature regarding propolis and its antimicrobial activity against microorganisms within dental biofilm, and evaluate the possibility of its employment as an adjunct to prevention and ultraconservative treatment of dental caries. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
0
23
0
2
Order By: Relevance
“…Nonrestorative treatments for caries aim to disrupt the decay process, particularly on smooth dental surfaces [33], and involve chemical and mechanical disorganization of biofilms by compounds such as fluoride and antimicrobial agents [34,35]. These treatments maintain the wholeness of the tooth and demonstrate adequate efficiency [36].…”
Section: Discussionmentioning
confidence: 99%
“…Nonrestorative treatments for caries aim to disrupt the decay process, particularly on smooth dental surfaces [33], and involve chemical and mechanical disorganization of biofilms by compounds such as fluoride and antimicrobial agents [34,35]. These treatments maintain the wholeness of the tooth and demonstrate adequate efficiency [36].…”
Section: Discussionmentioning
confidence: 99%
“…Propolis was used by man as a traditional medicine since 300 BC (Ghisalberti, 1979, Seidel et al, 2008, Sung et al, 2017, Trusheva et al, 2007, Uzel et al, 2005, Veiga et al, 2017). Researchers stated that the healing activities of propolis were identified by Roman (Machado et al, 2017) and Greek doctors (Elnakady et al, 2017, Ferreira et al, 2017) as well as other scientists, such as Dioscorides, Galen, Aristoteles and Pliny (Castaldo and Capasso, 2002, Crane, 1997, Dobrowolski et al, 1991, Toreti et al, 2013). Similarly, physicians used propolis efficiently for the treatment of injuries during Anglo-Boer battle (De Castro, 2001, Sforcin, 2007) as well as in World War II (Lotfy, 2006, Ramos and Miranda, 2007).…”
Section: History Of Propolismentioning
confidence: 99%
“…Similarly, the antibacterial activity takes place due to its active compounds such as, aromatic compounds (caffeic acid) and flavonoids (Parolia et al, 2010) . Moreover, propolis acts as a bactericidal agent, to stop division of bacterial cell, destroy cell wall, bacterial cytoplasm (Parolia et al, 2010) and stop protein synthesis (Lotfy, 2006, Machado et al, 2017). The component of propolis such as Pinocembrin shows antibacterial activity towards Streptococcus spp.…”
Section: Biomedical Application Of Propolismentioning
confidence: 99%
“…Previous studies also reporting that propolis have ameliorative role against the hepatic and renal damage caused by the oxidative stress damage (Wagh, 2013). Recent researchers reported that propolis has a cytoprotective role due to its antioxidant property, which attributed to its ingredients from phenol compounds (El-Guendouz et al, 2017;Machado et al, 2016). Also, many studies have demonstrated potential positive effects of propolis on glucose metabolism in human (Afsharpour, Hashemipour, Khadem-Haghighian, & Koushan, 2017), and experimental models of diabetic rats ( El Araby, Ahmed, & Zahkouk, 2017).…”
Section: Introductionmentioning
confidence: 96%